Poverty and Environmental Impacts of Electricity Price Reforms in Montenegro - Silva, Patricia (2012)
The creation of the Energy Community of South Eastern Europe in 2005 committed countries in South Eastern Europe to liberalize their energy markets in accordance to EU regulations. The Government of Montenegro is thus in the process of reforming its energy sector, which includes an electricity tariff reform. This paper analyzes the environmental and social impacts of an increase in residential electricity tariffs contemplated--which is expected to range anywhere from 40 to over 100% increase. As this analysis shows, such a significant price rise will impose a heavy burden on the poor households and it may adversely affect the environment. In an ex ante investigation of the welfare impact of this price increase on households in Montenegro, we show that the anticipated price increase will result in a very significant increase in households' energy expenditures. A simulation of alternative policy measures analyzes the impact of different tariff levels and structures, focusing on the poor and vulnerable households. Higher electricity prices could also significantly increase the proportion of households using fuelwood for space heating. Thus the level of fuelwood consumption should be carefully monitored under the electricity tariff reforms and the Government of Montenegro should combine the tariff reforms with a carefully evaluated set of policy measures to mitigate the effect of the electricity price increase on the poor.